2012
DOI: 10.1159/000334710
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Its Relation to Visceral and Subcutaneous Adipose Tissues in Healthy Male Koreans

Abstract: Aims: The purpose of the present study is to investigate the association of alcohol with visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) distribution and metabolic syndrome (MetS). Design: We conducted a cross-sectional study in 951 healthy male Korean participants who underwent health checkups. We measured the cross-sectional areas of VAT and SAT by computed tomography of the abdomen and performed a study of alcohol consumption based on questionnaire responses and a 24-hour dietary recall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 88 publications
3
21
0
1
Order By: Relevance
“…This observation might be explained because high intake of dairy products may reflect a dietary pattern being associated with VAT, and a separation of effects on VAT accumulation in multivariable regression by adjusting for intake of other food groups might thus miss associations between dairy products and AT volume. In line with our findings, in two other cross-sectional studies, alcohol consumption was positively associated with VAT (38,39) . Our study, however, does not support the observed inverse association between alcohol intake and SAAT reported in one of the two studies on women (39) .…”
Section: Discussionsupporting
confidence: 93%
“…This observation might be explained because high intake of dairy products may reflect a dietary pattern being associated with VAT, and a separation of effects on VAT accumulation in multivariable regression by adjusting for intake of other food groups might thus miss associations between dairy products and AT volume. In line with our findings, in two other cross-sectional studies, alcohol consumption was positively associated with VAT (38,39) . Our study, however, does not support the observed inverse association between alcohol intake and SAAT reported in one of the two studies on women (39) .…”
Section: Discussionsupporting
confidence: 93%
“…The effect of alcohol on fat metabolism remains controversial. In a cross-sectional study of healthy South Korean men, Kim et al [15] reported that alcohol consumption showed a significant association with increased VFA, which was independent of other factors. On the other hand, Fan et al [16] have reported that current alcohol consumption was associated with a lower prevalence of MS, irrespective of alcohol intake, and alcohol consumption had a favorable influence on HDL-C and WC in a Shanghai study.…”
Section: Innovations and Breakthroughsmentioning
confidence: 97%
“…43 Ethanol consumption has been identified as a risk factor for the deposition of abdominal or visceral adipose tissue. 44, 45, 46 Ethanol has been shown to suppress lipid oxidation, which results in the preferential deposition of nonoxidized lipids in the abdominal region. 47, 48 Our study suggests that CPEE alters lipid metabolism in offspring and causes increased adipocyte deposition in both the visceral and subcutaneous regions.…”
Section: Discussionmentioning
confidence: 99%